Implementasi Modul Kesadaran Diri Emosional dan Spiritual untuk Penurunan Tekanan Darah pada Pasien Hipertensi di Kelurahan Ditotrunan Lumajang: Implementation of Emotional and Spiritual Self-Awareness Module for Blood Pressure Reduction in Hypertensive Patients - Abu Bakar; Nur Arifah Astri; Dianis Wulan Sari; Rizki Fitryasari; Neisya Pratiwindya Sudarsiwi; Nauvila Fitrotul 'Aini; Ah Yusuf; Aziz Nashiruddin Habibie; Hakim Zulkarnain (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The priority health problem in Ditotrunan Village, Lumajang Regency, is the high prevalence of unmanaged hypertension. This condition causes degenerative diseases such as heart disease and stroke, which significantly reduce the community’s quality of life. Unhealthy lifestyles, including smoking, consuming foods high in salt and fat, and a lack of physical activity, further aggravate hypertension. Many residents also lack understanding of the importance of stress management and emotional and spiritual awareness in controlling blood pressure. Therefore, an emotional and spiritual self-awareness module was implemented as an intervention. The implementation involved delivering educational materials, training health cadres to use sphygmomanometers, and quantitatively monitoring the outcomes of the counseling sessions. The results showed an improvement in residents’ knowledge, increasing from an average score of 55.3 to 72.22. This community service program proved effective in enhancing public awareness of the role of emotional and spiritual self-awareness in managing hypertension.